Transitional justice in established democracies : A political theory - Winter, Stephen; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
Truth commissions, apologies, and reparations are just some of the transitional justice mechanisms embraced by established democracies. This groundbreaking exploration of political theory explains how these forms of state redress repair the damage state wrongdoing inflicts upon political legitimacy.
Keywords: Political science; Political theory; Comparative politics; Democracy; World politics; Political philosophy